The evolving landscape of immunohistochemistry in cervical and uterine carcinoma in gynecologic oncology: current status and future directions - Sumedha Gupta; Sana Ahuja; Dheer Singh Kalwaniya (Korean Society of Obstetrics and Gynecology, 2024)
Immunohistochemistry (IHC) has become an indispensable tool in routine gynecological pathology, particularly with the advancements in molecular understanding and histological classification of gynecological cancers. This evolution has led to new immunostainings for diagnostic and classification purposes. This review describes the diagnostic utility of IHC in gynecological neoplasms, drawing insights from literature reviews, personal experiences, and research findings. It delves into the application of IHC in resolving morphologically equivocal cases, emphasizing its role in achieving an accurate diagnosis. The selection of appropriate immunomarkers for common scenarios encountered in gynecological pathology aids pathologists in navigating complex cases. Specifically, we focus on cervical and endometrial malignancies, elucidating the molecular rationale behind the use of specific immunohistochemical markers. An updated overview of essential immunohistochemical markers provides knowledge for precise diagnosis and classification of gynecological cancers. This review serves as a valuable resource for clinicians and researchers involved in the management and study of gynecological malignancies, facilitating improved patient care and outcomes.